Bio-based materials for antimicrobial films in food applications: beyond the COVID-19 pandemic era - Perumal Pillai B.; Balasubramaniam B.; Gupta R.K.; Tyagi A. (My University, 2025)
The global pandemic caused by COVID-19 has increased awareness of the need for best practices to prevent the transmission of virus diseases. Antimicrobial films have been employed in packaging food items to minimize the spread of foodborne illnesses. However, the ongoing COVID-19 pandemic accelerated the demand for novel antimicrobial materials to prepare packaging films to minimize the virus spread through food items during processing and transportation. Considering the environmental pollution caused by single-use plastics, the demand for biodegradable polymers for packaging films has also increased in the current pandemic. This review aims to outline emerging bio-based antimicrobial materials and their incorporation into biopolymers as carriers for antimicrobial films, highlighting their potential as effective measures in preparing for future pandemics. © 2023 The Author(s).